Fault detection and diagnosis using correlation coefficients - 428635 Mak, Weng Yee (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2005